2017
DOI: 10.1242/jcs.198887
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of organelle ontogeny through a cell cycle revealed by whole-cell reconstructions using 3D electron microscopy

Abstract: The major mammalian bloodstream form of the African sleeping sickness parasite Trypanosoma brucei multiplies rapidly, and it is important to understand how these cells divide. Organelle inheritance involves complex spatiotemporal re-arrangements to ensure correct distribution to daughter cells. Here, serial block face scanning electron microscopy (SBF-SEM) was used to reconstruct whole individual cells at different stages of the cell cycle to give an unprecedented temporal, spatial and quantitative view of org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 45 publications
6
34
0
Order By: Relevance
“…AAT - just under the subpellicular microtubules -, the kinetoplast pocket is positioned underneath the nucleus not alongside it [39, 65]. In T. cruzi amastigotes 3D reconstructions revealed the mitochondrion has a horse shoe shape [18, 66] while T. brucei trypomastigotes in the vertebrate host have a poorly developed branching mitochondrion [17, 35, 36]. Direct glycolysis may be used in the presence of high glucose concentrations (such as the blood) reducing the size of the mitochondrion between morphological forms and increasing the size of the glycosomes, which was observed in Herpetomonas roitmani [67] and T. brucei [20, 21] suggesting the parasites switch from oxidative phosphorylation to glycolysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AAT - just under the subpellicular microtubules -, the kinetoplast pocket is positioned underneath the nucleus not alongside it [39, 65]. In T. cruzi amastigotes 3D reconstructions revealed the mitochondrion has a horse shoe shape [18, 66] while T. brucei trypomastigotes in the vertebrate host have a poorly developed branching mitochondrion [17, 35, 36]. Direct glycolysis may be used in the presence of high glucose concentrations (such as the blood) reducing the size of the mitochondrion between morphological forms and increasing the size of the glycosomes, which was observed in Herpetomonas roitmani [67] and T. brucei [20, 21] suggesting the parasites switch from oxidative phosphorylation to glycolysis.…”
Section: Discussionmentioning
confidence: 99%
“…The recent improvement in automated, high-throughput imaging techniques capable of high resolution 3D imaging overcomes these issues, and has led to 3D cellular architecture being characterised in Trypanosoma brucei [17, 3436], T. cruzi [37, 38] and T. dionisii [39]. A variety of morphological forms have been studied using a variety of different techniques that are available, including super resolution confocal microscopy [17], electron tomography [34, 37], serial block-face scanning electron microscopy [17, 36, 40], and focussed ion beam milling combined with scanning electron microscopy (FIB-SEM) [34, 38]. The primary difference between the latter two SEM-based techniques is that the serial block face method uses a knife to cut through the sample slice by slice permitting analysis areas in the order of hundreds of microns, while the FIB-SEM uses a beam of ions to cut through the sample permitting analyses on the scale of tens of microns.…”
Section: Introductionmentioning
confidence: 99%
“…Trypanosomatids possess multiple small glycosomes. Approximately 60-65 of these organelles with an average diameter of 0.27 µm have been reported for bloodstream-form T. brucei, distributed throughout the cell body, often in clusters, with the number increasing to ∼120 during parasite growth up to cell division Tetley and Vickerman, 1991;Hughes et al, 2017), whereas 50 glycosomes have been found in different life-cycle stages of T. cruzi (Soares and de Souza, 1988;Soares et al, 1989) (Figure 1E). Importantly, many of the glycosomal enzymes, as well as their sequestering inside the organelles have been shown to be essential for the viability of different trypanosomatids, rendering the organelles promising targets for new drugs to be developed (Galland and Michels, 2010;Barros-Alvarez et al, 2014;Dawidowski et al, 2017).…”
Section: Introductionmentioning
confidence: 94%
“…In T . brucei , organelle positioning and segregation during the cell cycle show a high degree of coordination and control [ 4 7 ]. Essential for pathogenicity, cytoskeleton remodelling occurs also during the parasite life cycle with major morphological alterations and changes in organelle positioning [ 8 11 ].…”
Section: Introductionmentioning
confidence: 99%